PENGARUH BIAYA CORPORATE SOCIAL RESPONSIBILITY TERHADAP LABA BERSIH PERUSAHAAN PADA PT. UNITED TRACTOR, Tbk - Wajongkere, Jessica; Kalangi, Lintje; Lambey, Robert (Universitas Sam Ratulangi, 2017)
Corporate Social Responsibility is a continuing commitment by the business community to act ethically and contribute to the economic development of the local community and the wider community, along with the improvement of the living standards of workers and their families (Wibisono 2007). The purpose of this study is to determine the influence of CSR costs on the company’s of net profit on PT. United Tractor, Tbk. This research uses simple linear regression analysis method. The type of data used is quantitative data obtained from secondary data. The results showed that there is no influence between the two variables (corporate social responsibility cost to net income of the company). Based on t-test, t-table> t-count (3,182> -2,074) and significant 0,130 where this value> 0,05 meaning there is no influence between independent variable to dependent variable.Keywords: Cost of Corporate Social Responsibility, Net income